Cassava cultivation and starch production in an Andean village - Strobosch, P (International Center for Tropical Agriculture, 1979)
A socioeconomic study was conducted on cassava cultivation and starch production in Cuatro Esquinas, Cauca (Colombia). The area is characterized by small landowners, with a cheap supply of labor, 2 rainy seasons, temperate climate, with cassava and coffee as the 2 most important cash crops. Twenty-four small-scale starch factories exist in the region, the constant demand for cassava has stimulated its production, although there has not been a major change in agricultural practices. Starch factories may be considered as simple or mechanical, processing 600 and 1200 kg of cassava/day, resp.; although in the latter, cassava shortage may reduce processing to 600-750 kg of cassava/day. Sharecropping is common. After initial manual land clearing, the soil is ploughed with oxen, there is no crop rotation, and the majority of farmers grow 3 consecutive crops of cassava in the same field. Intercropping systems used are cassava/plaintain, cassava/maize, cassava/beans and cassava/maize/beans. Chemical technology is limited to the application of insecticides to control ants; herbicides and fertilizers are not used due to negative attitudes and lack of sufficient knowledge on their advantages and disadvantages. Except for the small amount used for home consumption, all the cassava is sold locally to the starch factories. Credit facilities are limited. Present problems in cassava cultivation include the growing scarcity of cassava due to excessive demand and to a decrease in cassava yields (frog skin disease and deterioration of soil fertility), lack of capital and refusal of starch producers to buy fertilized cassava. (CIAT)